2017
DOI: 10.1007/s11523-017-0528-z
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Anaplastic Lymphoma Kinase (ALK) in Rhabdomyosarcoma (RMS) with the Second-Generation ALK Inhibitor Ceritinib

Abstract: BackgroundThe receptor tyrosine kinase (RTK) anaplastic lymphoma kinase (ALK) has been implicated in the tumorigenesis of rhabdomyosarcoma (RMS). However, the exact role of ALK in RMS is debatable and remains to be elucidated.ObjectiveTo determine the in vitro and in vivo effects and mechanism of action of the second-generation ALK inhibitor ceritinib on RMS cell growth.MethodsEffects of ceritinib on cell proliferation, wound healing, cell cycle, and RTK signaling were determined in alveolar and embryonal rhab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 44 publications
1
28
0
2
Order By: Relevance
“…IC 50 values were calculated using GraphPad Prism Version 5.03 software. Effects of treatment on cell migration were assessed by wound healing assays as previously described (van Erp et al 2017). Cell migration is depicted in relative gap size: gap size at t N /gap size at t 0 (t N = hours of treatment, t 0 = start of treatment).…”
Section: Cell Viability and Wound Healing Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…IC 50 values were calculated using GraphPad Prism Version 5.03 software. Effects of treatment on cell migration were assessed by wound healing assays as previously described (van Erp et al 2017). Cell migration is depicted in relative gap size: gap size at t N /gap size at t 0 (t N = hours of treatment, t 0 = start of treatment).…”
Section: Cell Viability and Wound Healing Assaymentioning
confidence: 99%
“…Drug synergy of combined olaparib and TMZ treatment was assessed as previously described (van Erp et al 2017). All drug concentrations were simultaneously combined in a non-constant ratio, and the combination index (CI) and dose reduction index (DRI) were calculated using CompuSyn software.…”
Section: Drug Synergy and Combination Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…The currently available IGF1R-targeted therapies have shown marginal efficacy in advanced clinical trials for OS and other tumor entities, presumably due to the activation of bypass signaling as a resistance mechanism. Previous reports have suggested that proto-oncogene tyrosine-protein kinase Src (Src) can mediate resistance to IGF1R inhibition in rabdomyosarcoma [12] and targeting Src with dasatinib sensitizes NSCLC cells to IGF1R tyrosine kinase inhibitors (TKIs) [13]. Src is phosphorylated in OS cells [14] and inhibition of Src activity by dasatinib induced apoptosis in OS cell lines and inhibited cell motility and invasiveness in vitro [15].…”
Section: Introductionmentioning
confidence: 99%
“…Src is phosphorylated in OS cells [14] and inhibition of Src activity by dasatinib induced apoptosis in OS cell lines and inhibited cell motility and invasiveness in vitro [15]. A synergistic effect of dasatinib (as Src inhibitor) and ceritinib (as IGF1R inhibitor) has been described in rabdomyosarcoma cell lines [12] and one phase I/II trial is recruiting rabdomyosarcoma patients to investigate the combined effects of the IGF1R antibody ganitumab and dasatinib (NCT03041701). However, the combination of ceritinib and dasatinib has not been tested in clinical studies so far.…”
Section: Introductionmentioning
confidence: 99%